Foliar application of selenium increased selenium accumulation, speciation, and bioaccessibility, as well as the yield and nutritional quality of sweet maize - Asamoah, Emmanuel Osei; Ssemalawa, Solomon Musoke; Danso, Ofori Prince; Wang, Yuanqi; Farooq, Muhammad Raza; Rao, Pincheng; Sun, Haoyuan; Guo, Yukun; Yin, Xuebin; Chen, Youtao (Frontiers in Plant Science, 2025)
IntroductionSelenium (Se) deficiency remains a significant global nutritional issue, emphasizing the need for efficient crop-based biofortification interventions.MethodsThis study examined the mechanistic responses of sweet maize (Zea mays L.) to foliar Se fertilization (0, 20, 40, and 60 g ha−1), focusing on antioxidant regulation, physiological traits, nutrient metabolism, Se speciation, and Se bioaccessibility.ResultsModerate Se doses (20–40 g ha−1) enhanced chlorophyll retention and photosynthetic efficiency, accompanied by increased activities of superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT), as well as 22.8% reduction in malondialdehyde (MDA), indicating improved redox homeostasis. These biochemical improvements facilitated higher assimilate accumulation, resulting in a 2–7% increase in fresh cob yield and enhanced levels of soluble sugars, amylose, protein, vitamin C, and key micronutrients (magnesium, iron, copper, manganese). However, excessive Se (60 g ha−1) caused oxidative imbalance, leading to decreased enzyme activity and reduced yield. Kernel Se concentration increased significantly with Se supply, dominated by selenomethionine (SeMet) (82.3% of total Se), exhibiting high in vitro bioaccessibility (35.6% gastric, 76.0% intestinal).DiscussionThe coordinated regulation of antioxidant defense and nutrient metabolism under optimal Se supply enhances both plant physiological performance and the nutritional bioefficacy of edible kernels, providing a mechanistic framework for sustainable Se biofortification.